The isoflavone fraction from soybean presents mRNA maturation inhibition activity. Issue 3 (4th March 2017) - Kurata, Masashi; Murata, Yuki; Momma, Keiko; Fouad Ali Mursi, Intisar; Takahashi, Masakazu; Miyamae, Yusaku; Kambe, Taiho; Nagao, Masaya; Narita, Hiroshi; Shibuya, Yasuyuki; Masuda, Seiji
Abstract: Recent findings indicate that mRNA splicing inhibitors can be potential anticancer candidates. We have previously established a screening system which monitors mRNA processing in order to identify mRNA processing inhibitors. Among a number of dietary resources, isoflavone fractions showed an inhibitory effect of mRNA processing. These findings demonstrate that a variety of dietary sources have an impact on mRNA biogenesis.